Growth-related changes in wheat (Triticum aestivum L.) genotypes grown under salinity stress. (28th July 2016) - Shahzad, Muhammad; Saqib, Zulfiqar A.; Hafeez, Farhan; Bilal, Muhammad; Khan, Sabaz A.; Asad, Saeed A.; Akhtar, Javaid
ABSTRACT: The sensitivity of crop genotypes determines the level of growth reduction by salinity. Effect of salinity levels (7.5 and 15 dihydrate m −1 ) using completely randomized design (CRD) with four replications per treatment were compared on germination, chlorophyll content, water potential, ionic sodium and potassium (Na +, K + ) balance, and other growth-related parameters of six wheat genotypes for varietal differences under long-term salinity stress. Chlorophyll contents at flowering stage and yield aspects at maturity of all the wheat genotypes decreased with increasing salinity. The maximum Na + concentration was observed at 7.5 and 15 dS m −1 in Bhakhar and Saher-2000, respectively, while minimum Na + concentration was observed for 9476. However, the maximum K + concentration and water potential was noticed in 9476 at 7.5 dS m −1 . Careful selection of salt-tolerant genotypes for field crops is an important perspective especially in the developing countries facing salinity problem. Our results revealed that the wheat genotype 9476 performed best regarding growth and physiological parameters compared to other wheat genotypes.